2017
DOI: 10.4049/jimmunol.1602186
|View full text |Cite|
|
Sign up to set email alerts
|

IL-33 Signaling Regulates Innate IL-17A and IL-22 Production via Suppression of Prostaglandin E2 during Lung Fungal Infection

Abstract: Members of the IL-1 family play protective and regulatory roles in immune defense against the opportunistic mold Aspergillus fumigatus. Here, we investigated the IL-1 family member IL-33 in lung defense against A. fumigatus. IL-33 was detected in the naïve lung, which further increased after exposure to A. fumigatus in a Dectin-1 independent manner. Mice deficient in the receptor for IL-33 (Il1rl1−/−) unexpectedly demonstrated enhanced lung clearance of A. fumigatus. IL-33 functioned as a negative regulator of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 51 publications
(71 reference statements)
4
33
0
Order By: Relevance
“…fumigatus challenge. In our report with IL-33 receptor-deficient mice, enhanced prostaglandin E 2 (PGE 2 ) production drove the observed elevations in IL-17A and IL-22 levels at 48 h postchallenge (32). We similarly observed elevated production of PGE 2 by lung cells from Chia Ϫ/Ϫ mice compared to WT mice at 48 h postchallenge ( Fig.…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations
“…fumigatus challenge. In our report with IL-33 receptor-deficient mice, enhanced prostaglandin E 2 (PGE 2 ) production drove the observed elevations in IL-17A and IL-22 levels at 48 h postchallenge (32). We similarly observed elevated production of PGE 2 by lung cells from Chia Ϫ/Ϫ mice compared to WT mice at 48 h postchallenge ( Fig.…”
Section: Resultssupporting
confidence: 53%
“…human peripheral blood mononuclear cell (PBMC) cultures may induce the antiinflammatory cytokine IL-1RA (30) or that A. fumigatus chitin is essentially inert (31). We recently reported that mice deficient in the receptor for the IL-1 family cytokine IL-33 demonstrated similarly enhanced A. fumigatus lung clearance in the absence of changes in lung cellularity (32). Mechanistically, we demonstrated this phenotype was a result of increased IL-1␣, IL-1␤, IL-6, IL-17A, and IL-22 production (32).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our studies demonstrate that tipping the IL-22/IL-22BP axis in favor of IL-22 is beneficial during influenza infection. Furthermore, targeting this axis has also proven useful in lung bacterial infections 4,19 and fungal infections, 46 as well as bacterial co-infections. 8,22 The question remains though-If IL-22 is so important in resolving infection, why is it so tightly controlled and is it safe to target?…”
Section: Discussionmentioning
confidence: 99%